Albumin-bilirubin grade may determine the outcomes of patients with very early stage hepatocellular carcinoma after radiofrequency ablation therapy. Issue 1 (January 2019) - Chen, Po-Chun; Chiu, Nai-Chi; Su, Chien-Wei; Huang, Yi-Hsiang; Hou, Ming-Chih; Lin, Han-Chieh; Wu, Jaw-Ching
Abstract : Background: To assess long-term prognoses of patients with solitary hepatocellular carcinoma (HCC) < 2 cm (the Barcelona Clinic Liver Cancer, BCLC stage 0) after radiofrequency ablation (RFA). Methods: We retrospectively enrolled 271 patients with BCLC stage 0 HCC who had undergone RFA at Taipei Veterans General Hospital from 2002 to 2016. Factors determining poor overall survival (OS) and recurrence after RFA were analyzed by Cox proportional hazards model. Results: After a median follow-up duration of 43.4 months, 76 patients had died. The cumulative 5- and 10-year OS rates were 67.1% and 56.4%, respectively. Multivariate analysis disclosed age > 65 years (hazard ratio [HR] 1.608, 95% confidence interval, [CI] 1.015–2.545; p = 0.043), platelet count < 100, 000/mm 3 (HR 1.704, 95% CI 1.027–2.828; p = 0.039), and albumin-bilirubin (ALBI) grade 2 or 3 (HR 2.191, 95% CI 1.261–3.805; p = 0.005) were the independent risk factors predicting worse OS. One-hundred twelve patients had tumor recurrence after undergoing RFA. Multivariate analysis showed that ALBI grade 2 or 3 (HR 1.825, 95% CI 1.288–2.585; p = 0.001) was the only one independent risk factor associated with poor recurrence-free survival (RFS) after RFA. Most of the subgroup analyses also demonstrated that patients with ALBI grade 2 or 3 had poorer OS and RFS than those with ALBI grade 1. Conclusion: For patients with BCLC stage 0 HCC, RFA could provide a long-term outcome with a 10-year overall survival rate of 56.4%. Moreover, the ALBI grade can discriminate prognosis in such patients.